Characterization, classification, and crop suitability of selected soils in the Ramain Subwatershed, Philippines - EDGEL O. ESCOMEN; ABDUL RACMAN M. MAPANDI; ALLYSA JOIE A. AMBOS; FELIX KENT NEIL J. SAN JOSE; ANALIZA C. OUANO; ALBERTO L. AMBOS; MELENCIO C. JALOVA JR. (Asian Journal of Agriculture, 2026)
Abstract. Escomen EO, Mapandi ARM, Ambos AJA, Jose FKNJS, Ouano AC, Ambos AL, Jalova Jr. MC. 2026. Characterization, classification, and crop suitability of selected soils in the Ramain Subwatershed, Philippines. Asian J Agric 10 (1): g100153. https://doi.org/10.13057/asianjagric/g100153. Sustainable agricultural development requires site- and soil-specific technologies. This study aimed to characterize, classify, and assess the land suitability of select soils in the Ramain Subwatershed, Philippines, derived from three representative pedons. Reconnaissance surveys, soil pedon identification and preparation, soil sampling, and physico-chemical analyses were conducted on select areas within the Ramain Subwatershed. Three representative pedons were analyzed through field characterization and physico-chemical analyses, followed by classification using the USDA Soil Taxonomy and land evaluation based on the FAO framework coupled with the parametric square-root method. Land suitability assessment of the three representative pedons indicated that no areas were highly suitable (S1) for the selected crops. Oil palm and banana showed moderate suitability (S2; LSI up to 67.19 and 56.68, respectively), primarily limited by drainage and soil texture. Several crops, including sugarcane and mango, were classified as marginally suitable (S3) due to constraints in texture and organic carbon. Meanwhile, Arabica coffee and cocoa were not suitable within the evaluated pedons because of combined climatic and physico-chemical limitations. These overarching constraints-particularly poor drainage, strong soil acidity, and low phosphorus availability-highlight the limitations of blanket agricultural recommendations and emphasize the necessity of targeted amelioration strategies to enhance productivity and sustainability.